Substrate-Selectivity in Catalytic Photooxygenation Processes Using a Quinine-BODIPY System - Fischer, Jérôme; Serier-Brault, Hélène; Nun, Pierrick; Coeffard, Vincent (Synlett, 2020)
Substrate selectivity by means of synthetic catalysts remains a challenging topic in chemistry. Here, a catalytic system combining an iodo-BODIPY photosensitizer and quinine was evaluated in the competitive photooxygenation of non-hydrogen and hydrogen-bond-donor substrates. The ability of quinine to activate hydrogen-bond-donor substrates towards photooxygenation was reported and the results were benchmarked with photooxygenation experiments in the absence of quinine.
Keywords: photooxygenation; singlet oxygen; substrate selectivity; BODIPY; oxidation